Cytotoxic Effects of Mangosteen Pericarp Extracts on Oral Cancer and Cervical Cancer Cells - Janardhanan, Sunitha (Asian Pac J Cancer Prev, 2020)
BACKGROUND: Despite immense advancements in treatment modalities, cancer remains a dreadful disease until the present. The major influencing factors behind the increased mortality rate of cancer are increased drug resistance and severe adverse effects caused by conventional cancer therapies. To overcome these limitations, the current medical field is focusing more on natural phyto-derived molecules to mitigate cancer. Mangosteen is a phytotherapeutic with potent anti-inflammatory and antioxidant properties. In the present study, we investigated the anticancer potential of the crude ethanolic extract of mangosteen against two dreadful forms of cancers, namely, oral cancer and cervical cancer, in vitro. METHODOLOGY: The pericarp of Garcinia mangostana or mangosteen was removed, air-dried, ground to fine powder, and macerated with ethanol. The extract obtained was then filtered and extracted with water for 48 h. The aqueous fraction thus obtained was then concentrated with a rotary evaporator at 40°C and dried with a freeze dryer. The anticancer efficacy of these extracts was investigated in human tongue squamous cell carcinoma (H357) cells and cervical cancer cells (HeLa) using the MTT assay, TUNEL assay, western blotting, and flow cytometry techniques. RESULTS: The crude mangosteen pericarp extract (MPE) significantly inhibited the growth of H357 and HeLa cells in a dose-dependent manner. Moreover, mangosteen induced early apoptosis in these cells after 48 h of incubation. Mangosteen also upregulated the expression of pro-apoptotic proteins, including caspases and Bax, and downregulated the expression of anti-apoptotic protein Bcl-2. CONCLUSION: The MPE exerted significant cytotoxicity against the H357 and HeLa cells in a dose-dependent manner and promoted their apoptosis. Hence, this natural phytoextract can be considered a potent anticancer agent for treating oral cancer and cervical cancer.